Interferon α induces a good molecular response in a patient with chronic eosinophilic leukemia (CEL) carrying the JAK2V617F point mutation - G. Helbig; B. Stella-Holowiecka; M. Majewski; M. Lewandowska; J. Holowiecki (Haematologica, 2007)
The JAK2 V617F point mutation is very rare in hypereosinophilic syndome and/or chronic eosinophilic leukemia. Here we report on a patient with chronic eosinophilic leukemia and detectable JAK2 mutant clone, who achieved a good molecular response to interferon α-2a after 4 months of treatment. The molecular response correlated with only moderate haematological improvement